Taecher Education Institute of Malaysia (IPGM) Lecturers Aspirations in Enhancing Capabilities in The Digital Innovation Field - Hairul Faiezi Bin Lokman; Shamsazila Binti Sa'aban; Siti Rosni Binti Mohamad Yusoff; Aliza Binti Adnan; Azerai Bin Azmi (Institut Pendidikan Indonesia, 2022)
Digital innovation in the education field is a necessity nowadays to face the challenges of theera of Industrial Revolution 5.0. With the threat of the Covid-19 pandemic, digital innovationis also seen as a driver to learning reform in new norms that make information technology anempowermentmediumforeducational institutionsaround the world. TeacherEducationInstitute of Malaysia (IPGM) is also optimistic about cultivating digital innovation amonglecturers to form a circle of educational enablers who are capable of implementing digitalinnovation for the exposure of prospective teachers (students). Thus, this survey study wasconducted toidentify the aspirations of IPGM lecturers to enhance their capabilities inimplementing digital innovation. Subjective items for open-ended questions were preparedusing Google Forms. The findings of this study showed that some of the IPG lecturers’aspirationsinenhancingtheircapabilitiesinthedigitalinnovationfieldincludedtheiraspirationsforinnovation,training,fundingassistance,infrastructureassistanceandcommercializationassistance.Keywords:DigitalInnovation,Aspiration,IPGLecturers